Subdoses de glyphosate no desenvolvimento de espécies arbóreas nativas - Pereira, Maria Renata Rocha; de Souza, Guilherme Sasso F. [UNESP]; Fonseca, Edson Diniz; Martins, Dagoberto [UNESP] (My University, 2015)
Recovery of degraded areas aims to provide the degraded environment favorable conditions for restructuring in an environment that is unable to regenerate itself and planting of tree seedlings is one of the effective ways to extend this process. However, native tree species have slow growth rate which increases the seedlings production time as well as decreases their competitiveness with weeds in areas of forests deployment. The aim of this study was to evaluate the effects of glyphosate reduced rates application on Psidium cattleyanum (yellow guava), Citharexylum myrianthum (pau-viola) and Cedrela odorata (cedro) seedlings development by analyzing its morphophysiological parameters. The experiment was carried out in greenhouse conditions and the experimental units consisted of one plant were conducted in 2.5L plastic pots and arranged in a completely randomized design with six replications. Treatments consisted of glyphosate application at 0, 7.5, 15, 30 and 60 g ha-1 using Scout® commercial formulation. Treatments application on these species seedlings was realized 120 days after seeds germination. Visual evaluations of plants phytotoxicity were realized at 7, 14 and 21 days after treatments application and plants survival, stomatal conductance, height, stem diameter and dry mass of shoots were evaluated 90 days after treatments application. Different doses of glyphosate did not cause plants phytotoxicity. Already, 30 and 60 g ha-1 of glyphosate provided greater increases in height, stem diameter and dry mass of shoots for Citharexylum myrianthum and Psidium cattleyanum, respectively.
Glyphosate reduced rates on the development of native tree species
Keywords: Cedrela odorata; Citharexylum myrianthum; Herbicide; Psidium cattleyanum